Thursday

April 24, 2014

April 24, 2014

Posted by **Shane** on Tuesday, August 6, 2013 at 11:54pm.

- maths -
**Steve**, Wednesday, August 7, 2013 at 5:01amS = (1-(1-x^3))^4 = (x^3)^4 = x^12

**Related Questions**

Maths - Expand ln(1+x) and ln(1-x) and hence deduce that ln((y+1)/(y-1))=[2/y]+[...

maths - Find the expansions of (1-x)^6 and (1+2x)^6 as far as the terms in x^3. ...

Math - Use Pascal's triangle to expand (a+b)^6 and hence find the binomial ...

maths - given that x+1/x=3 (a) expand (x+1/x)^3 and use your expansion to show ...

add maths - If f:x→4x+5,find the composite function f^2.Hence,find f^2(...

maths - If 5x4-14x³+18x²+40x+16=(x²-4x+8)(ax²+bc+c) find a,b and c and hence ...

maths inequalities... - Find the range of values of k for which the expression x...

maths - find the gradient of the tangent to the parabola y=4x-x^2 at (0,0) hence...

maths - y is partly constant and partly varies as the cube of x given that whenx...

maths - y is partly constant and partly varies as the cube of x given that whenx...